Предмет: Алгебра, автор: muhammadrozikov17

Даю 100 баллов пжжжж​

Приложения:

Ответы

Автор ответа: Evgenia4836
1

Ответ:

Объяснение:

\frac{x^2+1-10}{x-3}=\frac{x^2-9}{x-3}= \frac{(x-3)(x+3)}{(x-3)}= x+3

57+3=60

\frac{y+7-2y-2}{y^2-25}=\frac{-y+5}{y^2-25}=\frac{-(y-5)}{(y-5)(y+5)}=-\frac{1}{y+5}

-1/(5,7+5)= -1/10,7= -10/107

Автор ответа: nastamajkova49641
0

Ответ:

1) 60

2)\frac{-10}{107}

Объяснение:

1)  \frac{x^2+1}{x-3} -\frac{10}{x-3}=\frac{x^2+1-10}{x-3}=\frac{x^2-9 }{x-3} =\frac{x^2-3^2}{x-3}=\frac{(x-3)(x+3)}{x-3}  =x+3

Подставляем 57

57+3=60

2) \frac{y+7}{y^2-25} -\frac{2y+2}{y^2-25}=\frac{y+7-2y-2}{y^2-5^2}=\frac{-y+5}{(y-5)(y+5)}  =\frac{-(5-y)}{(y-5)(y+5)} =\frac{-1}{y+5}

Подставим 5,7

\frac{-1}{5,7+5}= \frac{-1}{10,7} =\frac{-10}{107}

Похожие вопросы